2020
DOI: 10.1590/1678-4685-gmb-2019-0374
|View full text |Cite
|
Sign up to set email alerts
|

The PAC-3 transcription factor critically regulates phenotype-associated genes in Neurospora crassa

Abstract: Transcription factors play an important role in fungal environmental adaptive process by promoting adjustment to challenging stimuli via gene modulation and activation of signaling networks. The transcription factor encoded by the pac-3/rim101/pacC gene is involved in pH regulation and is associated with a wide variety of cellular functions. The deletion of pac-3 affects fungal development. In Neurospora crassa, the Dpac-3 strain presents diminished aerial growth and reduced conidiation. However, the PAC-3-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Fungi contain advanced complex signal transduction networks allowing their adaptation to pH fluctuation, triggering the expression of several genes to facilitate their survival in a broad range of environmental conditions (Rossi et al, 2013 ; Martins et al, 2019a , b ). The pH shift and nutritional source are of great importance in maintaining dermatophyte growth (Martinez-Rossi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fungi contain advanced complex signal transduction networks allowing their adaptation to pH fluctuation, triggering the expression of several genes to facilitate their survival in a broad range of environmental conditions (Rossi et al, 2013 ; Martins et al, 2019a , b ). The pH shift and nutritional source are of great importance in maintaining dermatophyte growth (Martinez-Rossi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, assays carried out in A. nidulans demonstrated the activity of full-length PacC under acidic pH [ 72 ]. In addition, a recent study that profiled the gene modulation governed by Pac3 in the filamentous fungus Neurospora crassa demonstrated this transcription factor’s diverse metabolic and adaptive roles and its impact on the regulation of an additional 12 transcription factors [ 73 ]. Previous studies in dermatophytes have shown the involvement of the PacC signaling cascade in post-translational modifications (PTM), mainly related to glycosylation [ 74 ].…”
Section: Virulence Attributes Of Dermatophytesmentioning
confidence: 99%